Scattering investigation on the structure of γ-irradiated crosslinked polyethylene and filled silicone rubber materials - SONG Kun; TU Xiaoqing; LUO Xiang; LIU Dong (Fushe yanjiu yu fushe gongyi xuebao)
This review article highlights our group's use of γ-irradiation for crosslinking polyolefin systems and designing filled rubber systems. It emphasizes the application of synchrotron radiation and neutron scattering techniques for in situ studies on both material systems, providing an in-depth understanding of the relationship between the microstructure and properties of the materials. The article first illustrates how γ-ray irradiation initiates chemical reactions between polymer chains, promoting the formation of new chemical bonds to design and control the desired material systems. Based on this, our group has conducted in situ studies using major scientific facilities in China. These efforts not only showcase the advancements in the construction of major scientific facilities in China, including the three major neutron sources and synchrotron radiation sources, but also demonstrate the unique advantages of these facilities in promoting various fields, particularly in exploring the microstructure and dynamic processes of polymer-based materials.